Estimation of Volatility Functionals in the Simultaneous Presence of Microstructure Noise and Jumps - Mathias Vetter; Mark Podolskij (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
We propose a new concept of modulated bipower variation for diffusion models with microstructure noise. We show that this method provides simple estimates for such important quantities as integrated volatility or integrated quarticity. Under mild conditions the consistency of modulated bipower variation is proven. Under further assumptions we prove stable convergence of our estimates with the optimal rate n^(-1/4). Moreover, we construct estimates which are robust to finite activity jumps.
Keywords: 519; Bipower Variation; Central Limit Theorem; Finite Activity Jumps; High-Frequency Data; Integrated Volatility; Microstructure Noise